A importância dos metadados em bibliotecas digitais: da organização à recuperação da informação - Eduardo Ribeiro Felipe (2012)
Libraries have experienced a great change since the invention of the computer. The organization processes, maintenance, and search and recovery operations needed to be revised, in light of the new capacity of this new virtual capacity environment of information representation. This paper reports an investigation into the ability of metadata to contribute to the Digital Librarys environment: (a) allowing the definition of descriptors to identify a document; (b) establishing a standard for recording and retrieving information related to a specific item; (c) allowing recovery of documents through standard mechanisms for access. A prototype software was developed from this research, to show the ability of this mechanism to organize and allow retrieval of an electronic bibliographic item submitted to a selected pattern. The theoretical and methodological groundings had the digital libraries, metadata and organization of metadata standards as the principles. As a result of this research, the software implementation was successful in its proposal and was capable of performing the processes investigated in the methodology. The conclusions pointed to the value of these data structures, when aligned to an informational politics, enabling a cohesive collection and of easy retrieval access.